From Voices to Data: Tools for Creating a Multitask Atypical Speech Corpus through Citizen Science - Gioia, Caio Oliveira Di; Lembor, Victor Hugo S.; Fares, Samira; Macedo, Alessandra Alaniz (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Speech data from people with atypical speech patterns remain underrepresented in research, limiting the development of effective assistive technologies for communication support. The SofiaFala Ecoa project addresses this gap by designing and deploying an accessible, citizen-science-driven platform for the collaborative collection of a multitask atypical speech corpus. This initiative combines a redesigned mobile application, a web-based recording portal, and interdisciplinary outreach activities to engage participants with speech disorders, their families, and healthcare professionals. The system enables the capture of speech in multiple tasks—such as reading, repetition, and spontaneous speech—while supporting multimodal data integration. Our objectives are threefold: (1) to establish a scalable and inclusive infrastructure for gathering speech data; (2) to expand the availability of publicly shareable corpora of atypical speech; and (3) to foster community participation in research on assistive speech technologies. The contributions of SofiaFala Ecoa include the creation of a pilot corpus covering multiple speech tasks, the implementation of tools and protocols to ensure ethical and secure data collection, and the demonstration of feasibility through initial engagement metrics. By bridging accessibility, inclusivity, and technological innovation, SofiaFala Ecoa paves the way for improved AI-based speech technologies that reflect the needs of people with speech disorders.